The marketer's guide to public relations in the 21st century - Harris, Thomas L.; Whalen, Patricia T. (Texere Mason, Ohio, 2006)
The Marketer's Guide to Public Relations in the 21st Century provides a comprehensive overview of how public relations (PR) has evolved in the digital age. The book explores strategies that combine traditional PR with new media tools, helping marketers navigate the changing landscape of communication and brand management.